Teachers Job Satisfaction Through Narrative Experiences: The Role of Engagement, Emotional Intelligence, and Conflict Management - Susi Erviana; Ghufron Abdullah; Qristin Violinda; H. K. L Alvarez (International Journal of Educational Narratives, 2026)
Background. Teacher job satisfaction is essential for improving instructional quality and school performance. It is influenced by teacher engagement, emotional intelligence, and conflict management. Low satisfaction can reduce motivation and performance. However, prior studies often examine these factors separately, and empirical evidence in Indonesian junior high schools remains limited. Purpose. This study aims to examine the influence of teacher engagement, emotional intelligence, and conflict management on junior high school teachers’ job satisfaction in Kajen District, Pekalongan Regency, both partially and simultaneously. Method. This research employed a quantitative approach with an explanatory survey design. The population consisted of all junior high school teachers in Kajen District, with a sample of 123 respondents selected using proportional random sampling. Data were collected through a five-point Likert-scale questionnaire. Data analysis was conducted using simple and multiple linear regression after fulfilling the classical assumption tests. Results. The findings revealed that teacher engagement, emotional intelligence, and conflict management each had a positive and significant effect on teachers’ job satisfaction. Teacher engagement emerged as the most dominant factor, followed by emotional intelligence and conflict management. Simultaneously, the three variables had a very strong influence on job satisfaction, explaining 79.1% of its variance. Conclusion. Teachers’ job satisfaction is the result of the interaction between psychological and organizational factors. Therefore, efforts to improve job satisfaction should adopt a comprehensive approach that includes strengthening teacher engagement, developing emotional intelligence, and enhancing conflict management skills to support the improvement of educational quality.